Best Answer

-x^2 - 11x - 30

If you intended -1(x squared), making a quadratic equation, the solutions are -1 and +6.

Q: What is -1x plus 5x plus 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x - 5 + 3x = 1x + 15 3x + 3x -1x = 15 + 5 5x = 20 5x/5 = 20/5 x = 4

It's an algebraic expression that can be simplified to: x-5y

-1x^2 - 5x - 25/4 = -25/4 - 4x^2 + 5x + 25/4 = 25/4 + 4 (x + 5/2)^2 = 41/4

what is 6 in 5x+6

-1x-4-4x= -5x-4so it is -5x-4 -5x - 4this is done by combining like terms.

Related questions

4x - 3 - 5x + 7 = 6 4x - 5x = 3 - 7 + 6 -1x = 2 x = -2

its answer is probably -4.4 best of luckk!!!!!:)

Simplified: 5+1x

3x - 5 + 3x = 1x + 15 3x + 3x -1x = 15 + 5 5x = 20 5x/5 = 20/5 x = 4

If we recall that (5 cows plus 1 cow) = 6 cows, it immediately becomes apparent that5x plus 1x = 6x.

It can be simplified to: x-5y

It's an algebraic expression that can be simplified to: x-5y

-1x^2 - 5x - 25/4 = -25/4 - 4x^2 + 5x + 25/4 = 25/4 + 4 (x + 5/2)^2 = 41/4

what is 6 in 5x+6

-1x-4-4x= -5x-4so it is -5x-4 -5x - 4this is done by combining like terms.

5x + x = 5x Squared (5x^2) x + x equals 2 x's = 2 = squared - very simple & logic. no its not simple and logic 5x^2 is the result of 5x times x. 5x plus x is 6x. Think of the x as 1x not x so 1x + 5x= 6x. That's simple and logic.

bringing across the =, 5x = -10 so x = -2